Liberalism and nationalism: An analytical perspective on their relationship with Christianity - Rodríguez, Carmen; Rodríguez, Olga (Revista de Ciencias Sociales, 2022)
The aim of this article is to carry out a conceptual analysis of liberalism and nationalism and their relationship with Christianity. To this end, we employ a qualitative methodology, a theoretical-reflexive approach a documentary analysis, to determine why and how liberalism and nationalism have influenced Christianity. We conclude that nationalism, in addition to shaping secularization, has caused a rupture with Christian principles and values by elevating the national interest above other ideals, thus validating wars. Liberalism, meanwhile, has also shaped secularization, emphasizing the principle of subsidiarity and the value of democracy. For its part, the Catholic Church has rejected waging war and violating people’s essential rights in the name of nationalism. It has been flexible regarding the principle of subsidiarity, considering the role of democracy as a form of government and constituting the Vatican City State to escape from an exacerbated nationalism as in the case of fascism.